New insights in the disinfection of the root canal system using different research models - Pereira, Thaís Cristina (2020)
The present studies aimed to evaluate the influence of irrigation on biofilm removal from simulated lateral morphological features and in the intratubular decontamination. An Optical Coherence Tomography analysis of biofilm removal from Polydimethylsiloxane (PDMS) root canal models with lateral morphological features, such as isthmus and lateral canal-like structures was described for the first time (first study). Sodium hypochlorite at various concentrations and in different flow rates was used for root canal irrigation followed by a final irrigation with a buffer at a high flow rate. In addition, irrigant velocity inside the root canal model using different flow rates was measured by Computational Fluid Dynamics and correlated with biofilm removal. The irrigant flow rate had more influence on biofilm removal than the irrigant concentration. The irrigant velocity influenced biofilm removal, since in areas with higher velocities, more biofilm was removed. A high flow rate was also related to higher irrigant velocity inside the model. In the second study, a comparison of four different irrigation protocols regarding their ability to remove biofilm from the PDMS root canal model with lateral morphological features as well as from human dentine tubules using Optical Coherence Tomography or Confocal Laser Scanning Microscopy as evaluation methods, respectively, was described. The irrigation protocols used included syringe irrigation with a buffer solution (control group), a modified salt solution called Risa, Sodium hypochlorite and Ultrasonic activation of the buffer solution, followed by a final irrigation at a higher flow rate using the buffer solution. The mechanical effect of syringe irrigation showed to be a relevant factor to be observed when studying biofilm removal. Ultrasonic activation of the irrigant showed to be effective when the contact surface biofilm-irrigant was smaller. In the dentinal tubule model, besides the antimicrobial efficacy, a recolonization analysis was performed five days after the treatment. The analysis showed that the post treatment remaining biofilm was able to regrow inside the dentine tubules in a five day period without any extra nutrition. The antibiofilm effect of the buffer solution, Risa and sodium hypochlorite was tested on a biofilm grown on dentine disks. The biofilm thickness reduction and biofilm viscoelastic properties of the post treatment remaining biofilm were evaluated, showing no differences among the studied substances. The third study describes the influence of the irrigant, flow rate, irrigant refreshment and exposure time on biofilm removal from the root canal models with lateral morphological features by Optical Coherence Tomography. Sodium hypochlorite and demineralized water (control group) were used as irrigant solutions delivered in the root canal model with flow rates of 0.05 or 0.1 mL/s. Sodium hypochlorite and the higher flow rate presented greater biofilm removal from the isthmus like structures, whereas for the lateral canal, the flow rate had no influence. The samples were divided into different groups according to the irrigant solution refreshment number and that variable did not improve biofilm removal. Analysis of the sequential refreshments in the same biofilm showed a cumulative effect of irrigation on the biofilm removal.